PERILAKU PEMASARAN NABI MUHAMMAD SAW - Gunawan, Agung (University of Darussalam Gontor, 2013)
Basically marketing is an activity that tries to introduce the goods and services to consumers in order to facilitate them in choosing goods and services that become needs, all these activities should be mutually beneficial to both parties. Marketing activities will not be valid if it was contradicted to Islamic law. While that happens in contemporary times is the marketer has done duping of consumers in order to gain the benefit and win market competition by justifying a variety of ways, even though unlawful manner. The purpose of this discussion is to know about marketing behavior of Islam and the Prophet Muhammad SAW in its business activities. The result of the discussion for the real purpose of marketing was to introduce the actual marketing to customers about the advantages and disadvantages as well as benefits of a product. While the marketing behavior of the Prophet Muhammad put trust, tolerance and generosity, prohibition of exploitation, honesty, fairness and away against injustice, facilitate and provide relief as a basis for business success.